1993
DOI: 10.1143/jjap.32.4175
|View full text |Cite
|
Sign up to set email alerts
|

Film Thickness Dependence of Dielectric Property and Crystal Structure of PbTiO3 Film Prepared on Pt/SiO2/Si Substrate by Metal Organic Chemical Vapor Deposition

Abstract: A comprehensive analysis of gened relativistic spacetimes which admit a shearfree, irrotational and geodesic time-like coogruence is presented. The equations governing the models for a gened energy-momentum tensor are wrilten down. Coordinates in which the metric of such spacetimes takes on a simplified form are established. The general subwses of 'zero anisotropic stress', 'zero heat-flux vector' and 'two-component Ruids' are investigated. In particular, perfect-fluid Friedmann-Robertson-Walker models and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 11 publications
1
18
1
Order By: Relevance
“…[1][2][3][4] This thickness dependence is more pronounced in epitaxially grown thin films. Funakubo and co-workers 3 experimentally demonstrated that the lattice parameters and dielectric susceptibilities of epitaxially grown PbTiO 3 thin films were increasingly dependent on the film thickness with decreasing total thickness.…”
Section: ͓S0003-6951͑99͒05546-1͔mentioning
confidence: 93%
“…[1][2][3][4] This thickness dependence is more pronounced in epitaxially grown thin films. Funakubo and co-workers 3 experimentally demonstrated that the lattice parameters and dielectric susceptibilities of epitaxially grown PbTiO 3 thin films were increasingly dependent on the film thickness with decreasing total thickness.…”
Section: ͓S0003-6951͑99͒05546-1͔mentioning
confidence: 93%
“…The changes of dielectric properties, such as dielectric constant, remanent polarization and coercive field with film thickness has been reported for PbðZr; TiÞO 3 (PZT) [11,12], PbTiO 3 [13], BaTiO 3 [6], and ðBa; SrÞTiO 3 (BST) [9,10] thin films by many groups. The low frequency dielectric permitivity measurements were peformed on the KH 2 PO 4 (KDP) nanosize particle systems.…”
Section: Introductionmentioning
confidence: 99%
“…Low dielectric constant layers were easily generated by small mismatches of the lattice parameter and thermal expansion properties between the film material and substrate. 4),5) The thickness of this layer was reported as about 200 nm. As a result, the dielectric constant of the film decreases with decreases in film thickness.…”
Section: Origin Of the High Dielectric Properties Of Bt Nc 3d-assembliesmentioning
confidence: 99%
“…A low dielectric constant layer appears near the interfaces between the film and substrate. 4), 5) This phenomenon is known as the thickness effect of dielectric thin films. On the other hand, there are some reports that the interfaces of the dielectric nanoparticles and thin films have increased their ferroelectric and dielectric properties.…”
Section: Introductionmentioning
confidence: 99%